Adenosine-generating CD39+ plasmablasts predispose to successful infliximab therapy in pediatric IBD - Schnell, Alexander; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Schuh, Wolfgang; Regensburger, Adrian; Rauh, Manfred; Wölfle, Joachim; Hörning, André (Life Science Alliance, 2025)
B cells display several immunoregulatory mechanisms including the production of interleukin-10. Ectonucleotidases like CD39 and CD73 influence immune homeostasis by metabolizing eATP and generating immunosuppressive adenosine. The major objective was to examine the expression of those immunoregulatory molecules on B-cell subsets, and, more specifically, to determine their association with an infliximab (IFX) treatment in a pediatric inflammatory bowel disease (IBD) cohort. 42 IBD patients were assessed for IFX response after 12 mo of therapy and compared against 14 healthy controls (HC). Although IL10-producing plas-mablasts were decreased in IFX nonresponders (NRS), we de-tected an up-regulation of CD39 on plasmablasts and increased fractions of CD39/CD73-co-expressing naïve and memory B cells in responding patients (RS). In addition, B cells of responders proved to have superior ATP degradation capacities and aden-osine production before therapy initiation compared with NRS and HC. Moreover, IFX nonresponders had a marked deficiency of α4β7hi plasmablasts, whereas both cohorts had fewer CCR9-expressing plasmablasts. Consequently, CD39+ plasmablasts were decreased in biopsies of inflamed mucosal tissues, espe-cially in IFX nonresponders. Our results highlight the regulatory potential of CD39/CD73-expressing B cells in pediatric IBD and suggest CD39+ plasmablasts as a potential determinant of a successful immunosuppressive therapy with IFX.
CRIS-Team Scopus Importer:2025-05-02